A Lymphocyte Subset-Based Prediction Model for Refractory Community-Acquired Pneumonia in Immunocompetent Patients - Jingyuan Zhang; Xinyu Hu; Ailifeila Aili; Lei Pan; Xinying Xue; Xiaolan Chen (Diagnostics)
Background/Objectives: Refractory community-acquired pneumonia (r-CAP) has become a thorny issue in clinical practice, especially after the COVID-19 pandemic, even in immunocompetent patients, as conventionally defined. In this study, we aimed to identify the risk factors for immunocompetent patients with r-CAP. Methods: This was a single-center retrospective study. In total, we collected clinical data from 82 patients with r-CAP in whom the first-line antibiotic therapy failed and 82 patients with general CAP (g-CAP) who recovered with first-line antibiotics, matched at a ratio of 1:1, admitted to Beijing Shijitan Hospital, Capital Medical University, from 1 January 2022, to 31 December 2023. The differences between the two groups (clinical characteristics, peripheral blood cell count, lymphocyte subsets, and regular laboratory indicators) were analyzed using paired t, paired Wilcoxon, Chi-square, or Fisher’s exact tests, and univariate and multivariate logistics regression analyses were conducted to identify the independent risk factors. A model for predicting indicators with statistical significance was established and proved with the receiver operating characteristic (ROC) curve. Results: Warm season, a history of chronic obstructive pulmonary disease, longer time from onset to admission (TO-A), higher percentages of CD4+ T, CD8+ T, and double-negative T (DNT) lymphocytes, as well as higher levels of C-reactive protein (CRP), low-density lipoprotein cholesterin (LDL-C), serum sodium ion (Na+), and free-calcium ion (FCa2+) were regarded as independent risk factors, while T lymphocyte percentage (T%) and total cholesterol (TC) were identified as protective factors. The combined multivariate model using all the above factors proved to be sensitive and specific (AUC = 0.8711, p < 0.0001, R2 = 0.4235), and thus better than the respective univariate models. Conclusions: Increased CD4+ T%Lym, CD8+ T%Lym, and DNT%Lym, warm season, a history of COPD, longer TO-A, and increased levers of CRP, LDL-C, Na+, and FCa2+ potentially cause CAP to be refractory, while the T lymphocyte count, namely, the overall cellular immunity, was impaired in r-CAP patients, and increased TC levels could be beneficial to pneumonia recovery.